Influence of end user development on software project estimation - Srivastava, Archana; K. Singh, Dr.; Syed Qamar Abbas, Dr (International Journal of Engineering and Technology, 2018)
Use Case Point Method (UCP) is used to estimate software development effort. UCP uses a project’s use cases to produce a reasonable estimate of a project’s complexity and required man hours. Advance Use Case Point Method (AUCP) is an extension of UCP. AUCP extends UCP by adding the additional effort required in incorporating end user development (EUD) features in the software for overall project effort estimation. Today user needs are diverse, complex, and frequently changing hence need of EUD is also increasing. EUD features if incorporated in the software increases end user satisfaction exponentially but incorporating EUD features increases design time complexity and increases the effort significantly based on the end users requirements. This paper provides a case study to demonstrate the comparative analysis of UCP and AUCP using paired t-test. It also observes that there can be on an average 20% increase in overall effort of development on adding EUD features.